Pelanggaran Inggris terhadap Konvensi Basel: Digital Dumping Ground di Nigeria - Haryadi, Yulius; Windiani, Reni; Rosyidin, Mohamad (Journal of International Relations, 2017)
This research identifies the causes of the United Kingdom’s violation of the Basel Convention in the case of disposal of electronic waste from United Kingdom to Nigeria in 2003-2010. This research is using grounded theory, the research method draws conclusions and theories from the empirical data. The results of this research showed that the UK's non compliance to the Basel Convention lack of the UK's commitment to environmental and health issues. UK often received a warning from the European Commission and other countries regarding their transgressions of environmental issues at the global and domestic level since UK is more focusing on traditional issues of international relations, such as military, security and political issues. In addition, Nigeria's population demand on used electrical and electronic equipment is quite high, because many citizens are involved in this sector, either as recyclers or consumers. This is why UK continues to dispose its electronic waste to Nigeria.